GAMBARAN PLACE ATTACHMENT PADA MASYARAKAT DAERAH MAKAM SUNAN GIRI GRESIK - Nurul Avifah; Muhimmatul Hasanah; Fatchul Munir (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2022)
Humans have a attach with a place called a place attachment. In this study, researchers aimed to find out the picture of place attachment in the community of the Grave of Sunan Giri which was expressed through feelings and actions carried out. This research used a qualitative method with the subject of the study, namely the community of the Grave of Sunan Giri area which was selected through purposive sampling in accordance with predetermined characteristics so that as many as 5 research subjects were obtained. The collection carried out in this study used interview and observation methods. The credibility of the data used uses source triangulation by comparing the subject's interview data with interviews with significant other. Based on the research conducted, the results were obtained that there was a picture of place attachment in the community of the Grave of Sunan Giri which was shown through the feelings and actions carried out by the subject. The place attachment that occurs in the community Grave of Sunan Giri area is in the form of positive and negative emotions felt during their stay in the Grave of Sunan Giri area and actions to protect the Grave of Sunan Giri area.